Relationships Between Candida auris and the Rest of the Candida World—Analysis of Dual-Species Biofilms and Infections - Monika Janeczko; Tomasz Skrzypek (Pathogens)
In this study, we investigated the interactions between Candida auris and C. albicans, C. tropicalis, C. glabrata, and C. krusei in mixed infections. Initially, these interactions were studied qualitatively and quantitatively in dual-species biofilms formed in vitro. The MTT assays, determination of the total CFU/mL, and SEM analysis showed that C. auris interacted differentially with the other Candida spp. during the dual-species biofilm formation. Depending on the stage of the biofilm development, C. auris was found to be a particularly dominant species during its interaction with the C. krusei biofilms but significantly submissive in the C. auris-C. albicans biofilms. These studies were then extended to in vivo host models of experimental candidiasis. G. mellonella larvae were inoculated with monotypic and heterotypic suspensions of Candida. The survival rates and quantification of fungal cells in the hemolymph showed that the highest mortality was exhibited by larvae in the C. auris-C. albicans co-infection (100% mortality after 36 h). The CFU/mL values of C. auris from the larval hemolymph were lower in the interactive groups compared to the mono-species group. As a newly emerging species, C. auris persists in environments in the presence of other Candida species and is involved in both competitive and noncompetitive interactions with other Candida species during biofilm formation and development of experimental candidiasis.